1999
DOI: 10.1111/j.1601-0825.1999.tb00085.x
|View full text |Cite
|
Sign up to set email alerts
|

The World Health Organization initiative on noma

Abstract: Oro‐facial noma is a worldwide scourge in a context where the World Health Report 1998 gives a global incidence of 140 000 cases, a prevalence in 1997 of 770 000 persons surviving with heavy sequelae. The background and the five steps of the WHO oral health programme to control noma including: (i) ensuring training and awareness on early diagnosis and treatment for each public health structure, (ii) raising awareness and informing populations, (iii) promoting epidemiological research, (iv) promoting aetiologic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
58
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(59 citation statements)
references
References 8 publications
1
58
0
Order By: Relevance
“…10 In 1997, worldwide extensiveness of those living with the sequelae of noma was placed at 770,000. 5 Recent research indicates that noma is almost exclusively found in sub-Saharan Africa and in west Africa along the area running from Senegal across West Africa into Sudan and Ethiopia, coinciding with the so called ''meningitis belt''. Sporadic reports of solitary adult cases of noma seem to be a secondary disorder in individuals affected with complex diseases such as HIV/AIDS and other diseases.…”
Section: History and Epidemiologymentioning
confidence: 99%
See 1 more Smart Citation
“…10 In 1997, worldwide extensiveness of those living with the sequelae of noma was placed at 770,000. 5 Recent research indicates that noma is almost exclusively found in sub-Saharan Africa and in west Africa along the area running from Senegal across West Africa into Sudan and Ethiopia, coinciding with the so called ''meningitis belt''. Sporadic reports of solitary adult cases of noma seem to be a secondary disorder in individuals affected with complex diseases such as HIV/AIDS and other diseases.…”
Section: History and Epidemiologymentioning
confidence: 99%
“…Noma is a disease of shame, so those affected are ignored rather than being taken for the medical care. 5 Noma is truly an inexplicable disease and the understanding of it is confined. To incorporate the preventive measures and to develop an early treatment regimen for noma, a better understanding of the aetiopathogenesis is required.…”
Section: Introductionmentioning
confidence: 99%
“…Noma (from the Greek "'to devour'") is a severe infectious disease usually found in extreme sanitary conditions, such as many areas of rural Iran in the 1960s (Ronaghy and Nasr, 1970;Asadi-Lari et al, 2004;Movahedi et al, 2009). Often preceded by a systemic infection (such as measles or malaria), it develops at a young age (peak age 1−4 years) and in conditions of malnutrition, poor local hygiene and medical isolation (Tempest, 1966;Bourgeois and Leclercq, 1999;Baratti-Mayer et al, 2003;Marck, 2003;Enwonwu et al, 2006;Feller et al, 2013). Studies have established a link between noma and the country's economic development, especially the enforcement of public health policies (Bourgeois and Leclercq, 1999;Marck, 2003;Enwonwu et al, 2006).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…According to the World Health Organisation (WHO) noma has an annual global incidence of 14000 cases (5). Most of these cases are found in the poor regions of sub-Saharan Africa in the socalled noma belt, suggesting that noma is a tropical disease.…”
Section: Introductionmentioning
confidence: 99%
“…Noma has a high mortality rate of 90% in untreated cases and the survivors of the disease suffer from the stigma of debilitating disfigurement and functional defects such as trismus, oral incontinence and speech problems 1-5 These cases are estimated to be numbering about 770,000 all over the world and would require very challenging and prolonged reconstructive options (1)(2)(3)(4)6,10). Although noma is predominantly a childhood disease adult cases especially in association with secondary immunodeficiency including that from HIV infection have been reported (3,5,9). Literature on noma from Kenya has been scanty.…”
Section: Introductionmentioning
confidence: 99%